Modelling of slope processes on karst - Uroš Stepišnik; Gregor Kosec (Acta Carsologica, 2011)
The present paper is concerned with the modelling of the karst slope processes. A simple straightforward one dimensional physical model is introduced in order to assess basic behaviour of the slope development. The model takes in account mass continuity of weathered material, the mechanical and chemical weathering of the bedrock. The paper focuses on the slope formation with respect to the ratios between different magnitudes of governing processes (mechanical and chemical weathering and mass movement). The introduced approach represents a first step in understanding slope processes and does not pose a realistic quantitative comparison with field measurements. However, the results gathered with the model show good qualitative agreement with the field observations. Three different representative cases are studied: dominant mechanical weathering case, balanced mechanical and chemical weathering case and dominant chemical weathering case.